Structural modeling of tumor necrosis factor: A protein of immunological importance. (30th March 2017) - Roy, Urmi
Abstract: Tumor necrosis factor (TNF) is a multifunctional pro‐inflammatory cytokine responsible for various immunoregulatory activities. Upon binding with its receptor, TNF triggers multiple complex signaling pathways such as the activations of nuclear factor kappa B and caspase cascade, which are the leading determining factors for cell survival or cell death. The present work studies certain modeling aspects of the TNF, with comparative structural analyses of the wild and mutant types of this protein. Additionally, nanoscale molecular dynamics simulations are performed to assess the structure–property relationships of proteins as functions of time.